Multiprofessional residency as a strategy for training human resources from an interprofessional perspective in perinatal health (Research, Society and Development, 2020)
Objective: To know the perceptions of the actors involved in a Multiprofessional Residency program on the factors that influence interprofessional education. Method: exploratory, qualitative study, conducted with 18 graduates and 17 tutors from a multiprofessional residency program. The data were obtained through a questionnaire with open and closed questions, applied in a virtual environment and the data analysis carried out through thematic analysis. Results: although interprofessional education is not encouraged in the graduation of half of the participants, most preceptors are able to develop their activities with residents in this perspective and this is also perceived by the graduates. Facilitating strategies and barriers were perceived to increase interprofessional education in the Program and, in addition, professionals suggested new ways to achieve this goal. Conclusion: interprofessional education is present in the Program, meeting the principles and guidelines of the Unified Health System, building collective knowledge and with the potential to improve care quality. Based on the knowledge of the barriers to this practice, we can resort to strategies designed in groups to overcome them. This model of education should be developed and encouraged in the undergraduate and graduate courses of institutions that train human resources for health.